First report of leaf blight of Avena strigosa caused by Pyrenophora avenicola in Japan - Sugawara, Koya; Nishimoto, Kiyoshi; Uwatoko, Naohiro; Tsukiboshi, Takao (Plant disease, 2024)
Black oat ( Schreb.) is used as a cereal crop, forage crop or green manure in temperate regions. In Japan, it is mainly cultivated in Hokkaido island and, because of the vigorous initial growth and ability to suppress the proliferation of plant pathogenic nematodes (Uesugi et al. 2018), its use is recently increasing. In November 2021, a leaf spot and blight disease was observed in the grass cultivated in Kitahiroshima city (N43°0, E141°31). At first, blackish brown spindle-shaped or elliptical lesions, about 3 to 5 × 1 to 2 mm were formed on leaves, and they expanded by forming yellowish-brown halos around them, eventually resulting in leaf blight later on (Fig.1), damaging 5-10 % of leaf area, varied by cultivar. The lesions were excised, surface-sterilized, and incubated on water agar under near-UV light. Three single-spore isolates of -like fungus were obtained from the lesions and deposited at the NIAS Genebank, Japan (https://www.gene.affrc.go.jp/index_en.php) as MAFF511692, 511693 and 511694. The sequences of ribosomal RNA gene (rDNA) and its internal transcribed spacer (ITS), and the gpd sequences of the isolates were analyzed as described by Marin-Felix et al. 2019. The rDNA-ITS sequences (GenBank accession no. LC769170, LC769171 and LC769172) of the isolates matched with that of the ex-type strain of (MK539972) isolated from seed. The sequences of the gpd (accession no. LC795722, LC795723 and LC795724) matched well with that of the ex-type strain (MK540180). Conidiophores of the isolates were septate, straight or flexuous, pale brown to olivaceous brown, 81.4 to 125.7 × 4.2 to 6.5 (ave. 106.4×5.7µm, n=50) µm, with hyaline vegetative hyphae (Fig.2). Conidia were slightly verrucose, cylindrical to obclavate, pale brown to olivaceous brown, 42.2 to 78.5 × 9.0 to 13.3 µm (ave. 56.9 ×10.4µm, n =50) and 2 to 7 distoseptate. This description overlap with the original description of (Marin-Felix et al. 2019) and the leaf spot pathogen of reported in China (Chen et al. 2022). The fungus was identified as on the basis of morphology and molecular phylogenetic analysis. To produce inoculum, the isolate MAFF511692 was grown on V8 juice agar at 25°C under near-UV light for 7 days. Five plants each of cv. 'Soil saver', 'New oats' of (Kaneko seeds co.) and 'New almighty' of (Snow brand seed co.) were grown in a greenhouse for approximately 14 days and then inoculated by atomizing them with the conidial suspension (10 conidia/ml) at the five-leaf stage. Five plants of each cultivar sprayed with sterilized distilled water served as the control. Inoculated plants were covered with plastic bags for 24 h at 25°C. After 5 days, blackish brown elliptical lesions developed on the leaves of all inoculated plants of both cultivars of (Fig. 3) and , implying broad pathogenicity of the fungus to species and cultivars of plants. Halo was not observed, maybe due to fewer stress in the greenhouse environment. Controls remained asymptomatic. The produced lesions were incubated as described above and the reisolated fungus was identified as based on the morphology, confirming Koch's postulates. To our knowledge, this is the first report of leaf blight caused by on black oat in Japan.